Disentangling Natural and Anthropogenic Forms of Mortality and Serious Injury in a Poorly Studied Pelagic Dolphin - Ashe, Erin; Williams, Rob; Morton, Alexandra; Hammond, Philip S. (Frontiers in Marine Science, 2021)
Killer whale (Orcinus orca) populations specialize in both prey and prey acquisition tactics around the world and may be a primary evolutionary driver of the habits of small cetaceans. Entanglement in fishing gear is the most significant anthropogenic threat to the survival of cetaceans worldwide. Distinguishing between natural and human-caused sources of mortality and injury is a key task in marine mammal conservation and management. In British Columbia, Canada, mammal-eating killer whales co-occur with Pacific white-sided dolphins (Lagenorhynchus obliquidens). Bycatch mortality rates are unknown here due to lack of systematic fisheries observer coverage. Drawing from more than three decades of first-hand observations of killer whale attacks on Pacific white-sided dolphins, we identify common themes with respect to predatory behavior of killer whales and anti-predatory responses of dolphins. With input from veterinary pathologists, we outline clues to distinguish killer whale rake marks from scars and wounds likely to be caused by fishery interactions. We examined photographs of 415 well-marked Pacific white-side dolphins for evidence of injuries and scars consistent with either killer whale attacks or fishery interactions. In this case study, healed scars from interactions with killer whale predators were 8x more common than scars from fishery interactions (3.9% vs 0.5%), suggesting that predation is a much bigger threat to Pacific white-sided dolphins in the study area than anthropogenic impacts, or that dolphins are much less likely to survive a fishery interaction than a predation attempt. To advance our knowledge on poorly studied species, multiple lines of evidence will be needed.